ChemInform Abstract: Oxidative Rearrangement of Cyclobutanone Derived N, O‐Ketals Leading to Pyrrolidone Derivatives. Issue 35 (September 2015) - Murai, Kenichi; Endo, Daisuke; Kawashita, Norihito; Takagi, Tatsuya; Fujioka, Hiromichi
Abstract The halogen‐induced rearrangement proceeds via an iminium ether intermediate.